PENERAPAN VISUAL MERCHANDISING SEBAGAI ALAT KOMUNIKASI PEMASARAN PRODUK WAKAi SHOES STORE DI TUNJUNGAN PLAZA 3 SURABAYA - Arafah, Ananda Tenri (Jurnal Art Nouveau, 2014)
Abstract: Visual Merchandising at Wakai shoes store is enough to attract the visitors Tunjungan Plaza 3 Surabaya, this is because the new brand is present in the midst of a more senior brand competition. As its major new brand in Surabaya, of marketing communication activities should be applied. One of his lines is the method of visual merchandising. This study aims to describe how the implementation of visual merchandising as a marketing communication tool products Wakai shoes store in Tunjungan Plaza 3 Surabaya, and to know the obstacles in the implementation of visual merchandising. This research is a descriptive qualitative study aimed to gain insights into what the application of visual merchandising. Data collection techniques by conducting observations, interviews, and documentation. The sampling method was used a nonprobability by purposive sampling technique. The results showed that most of the informant liked the design and implementation of visual merchandising Wakai in Tunjungan Plaza 3 Surabaya. They were entertained by the visual appearance and attributes, color, and atmosphere in the store is iconic, attractive decor color selection, arrangement displays, furniture store attributes, good graphics, lighting fitting, and warm temperatures in the store is one of the key informant liked display of visual merchandising Wakai Tunjungan Plaza 3 Surabaya. Â Keywords: Visual Merchandising, Marketing Communications, Wakai